Application of deep learning algorithm for spectrum sensing in cognitive radio - Zhang, Zihan (Nanyang Technological University, 2024)
In recent years, with the development of related technologies, the requirements for frequency resources are also increasing day by day, but due to the scarcity of wireless resources, the utilization of resources is limited. With the increasing number of users and the emergence of many electromagnetic devices, radio frequency resources are increasingly scarce. Therefore, the effective utilization of spectrum-related techniques for the monitoring and management of frequencies has emerged as a prominent and actively pursued subject in contemporary scientific research.